Toward Ensuring Health Equity: Readability and Cultural Equivalence of OMERACT Patient-reported Outcome Measures - DURUÖZ, MEHMET TUNCAY (J RHEUMATOL PUBL CO, 2015)
Objective. The goal of the Outcome Measures in Rheumatology (OMERACT) 12 (2014) equity working group was to determine whether and how comprehensibility of patient-reported outcome measures (PROM) should be assessed, to ensure suitability for people with low literacy and differing cultures. Methods. The English, Dutch, French, and Turkish Health Assessment Questionnaires and English and French Osteoarthritis Knee and Hip Quality of Life questionnaires were evaluated by applying 3 readability formulas: Flesch Reading Ease, Flesch-Kincaid grade level, and Simple Measure of Gobbledygook; and a new tool, the Evaluative Linguistic Framework for Questionnaires, developed to assess text quality of questionnaires. We also considered a study assessing cross-cultural adaptation with/without back-translation and/or expert committee. The results of this preconference work were presented to the equity working group participants to gain their perspectives on the importance of comprehensibility and cross-cultural adaptation for PROM. Results. Thirty-one OMERACT delegates attended the equity session. Twenty-six participants agreed that PROM should be assessed for comprehensibility and for use of suitable methods (4 abstained, 1 no). Twenty-two participants agreed that cultural equivalency of PROM should be assessed and suitable methods used (7 abstained, 2 no). Special interest group participants identified challenges with cross-cultural adaptation including resources required, and suggested patient involvement for improving translation and adaptation. Conclusion. Future work will include consensus exercises on what methods are required to ensure PROM are appropriate for people with low literacy and different cultures.
Keywords: HEALTH EQUITY; MUSCULOSKELETAL CONDITIONS; RHEUMATOLOGY; LITERACY; CULTURAL ADAPTATION; QUALITY-OF-LIFE; LITERACY LEVELS; ADAPTATION; TRANSLATION; INSTRUMENTS; GUIDELINES; PEOPLE